Bardoxolone methyl attenuates acetaminophen-induced acute kidney injury by suppressing oxidative stress, inflammation and apoptosis - Teksen, Yasemin; Kadıoglu, Emine; Ozatik, Fikriye Yasemin; Ozatik, Orhan (Annals of Medical Research, 2024)
Aim: Nuclear factor erythroid 2-related factor 2 (Nrf2) is important in ameliorating several diseases caused by oxidative stress and inflammation, including acute kidney injury (AKI). Bardoxolone methyl (BM) is powerful Nrf2-activating drug. This study evaluated the renoprotective effects of BM against acetaminophen (N-acetyl-para-aminophenol; APAP) induced AKI in rats.Materials and Methods: Forty-two rats were evenly split into 6 groups; control (saline), vehicle (sesame oil), APAP, APAP+N-acetylcysteine (NAC) (160 mg/kg), APAP+BM (5 mg/kg), and APAP+BM (10 mg/kg). Kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), tumour necrosis factor-α (TNF-α) levels, total oxidant status (TOS) and total antioxidant status (TAS) were analysed in the kidney tissue. Histopathology was performed on glomerular and tubular structures. For apoptosis, caspase-3 was assessed by immunohistochemistry.Results: APAP caused an increase in KIM-1, NGAL, TNF-α, oxidative stress and apoptosis and histopathological changes in the kidney. BM dose-dependently reduced APAP-induced AKI, including renal oxidative stress, histopathology and apoptosis. BM also decreased KIM-1, NGAL and TNF-α in the kidney.Conclusion: BM has demonstrated therapeutic effects against APAP-induced AKI by enhancing the antioxidant system, modulating inflammatory cytokines and inhibiting apoptosis in rat kidney.
Keywords: Acetaminophen; Bardoxolone methyl; N-acetyl cysteine; Acute kidney injury; Nuclear factor erythroid 2-related factor 2